Pengembangan Modul Mata Kuliah Statistika Pendidikan di Fakultas Keguruan dan Ilmu Pendidikan Universitas Batanghari Jambi - Diliza Afrila; Akhmad Faisal Hidayat (Universitas Batanghari Jambi, 2020)
This study aims to determine (1) the process of developing Statistics Education module modules at the Teaching and Education Faculty of Batanghari University Jambi, (2) The eligibility of the Education Statistics module at the Teaching and Education Faculty of Batanghari University Jambi based on the assessment of material experts and media experts , and (3) Eligibility for Educational Statistics modules in the Teaching and Education Faculty of Batanghari University Jambi based on student assessment. The research the researcher carried out included research and development methods by adapting the ADDIE development model. The data collection instrument that researchers use is a questionnaire, which aims to measure the feasibility of the media, both by material experts, media experts, and students as material for evaluating the product / learning media developed. The results of the study show that (1) The process of developing the Education Statistics module modules refers to the ADDIE development model, namely (a) Analysis, namely needs analysis, material analysis, and competency analysis, (b) Design (Design), i.e. gathering the object of design and preparation of assessment instruments, (c) Development, namely the creation of instructional media, material validation, material revision, media validation, and media revision, (d) Implementation, namely One to One, Small Group, and Field Test, and (e) Evaluation, which analyzes the assessment of material and media experts, analyzes the assessment of students, and the final product, (2) The feasibility of Education Statistics modules based on material and media expert assessments, namely (a) Expert assessment material before revision obtained an average of 4.01, so it is in the feasible category. Meanwhile, the material expert assessment after the revision obtained an average of 4.53, so that it was in the very feasible category, and (b) The media expert assessment before the revision obtained an average of 4.09, so that it was in the feasible category. Meanwhile, the assessment of media experts after the revision obtained an average of 4.53, so that it was in the very feasible category, and (3) The feasibility of the Education Statistics modules based on student assessment, namely (a) One to One gained an average of 4.49 with TCR 89, 78 so that it is in the good category, (b) Small Group obtains an average of 4.16 with TCR 83.24 so that it is in the good category, and (c) Field Test obtains an average of 4.44 with TCR 88 , 71 so it is in the good category.